Green solvent assisted preparation of one-dimensional CsPbBr3 nanocrystals with a controllable morphology for cyan-emitting applications. Issue 44 (1st November 2021) - Lai, Wenwei; Wu, Chuanli; Li, Wenhui; Han, Xiuxun
Abstract : Upon tuning the polarity of antisolvent medium, the length of CsPbBr3 NCs realizing the conversion from nanorods to NWs. Furthermore, the width of the NWs can be adjusted feasibly via the overgrowth of CsPbBr3 NWs. Abstract : The ligand assisted reprecipitation (LARP) approach is a convenient method for synthesizing CsPbX3 NCs at room temperature. However, several remaining challenges limit its further development, such as the utilization of toxic solvents and fast crystallization brings colloidal uncontrollable synthesis issues. In this work we apply the principles of green chemistry to the LARP technique for synthesizing CsPbBr3 NCs under ambient conditions in a controllable way. Through the variation of non-toxic ester solvents with different polarity and reaction time, we demonstrate the size tunability of one-dimensional (1D) CsPbBr3 nanocrystals synthesized in a green solvent system. Due to the strong quantum confinement effect, the obtained CsPbBr3 NCs exhibited a wide photoluminescence emission (471–508 nm) and high quantum yield up to 78%. Interpretations on the related growth mechanism of CsPbBr3 nanocrystals in a polarity-mediated solution are suggested for exploring effective strategies towards high-quality inorganic perovskite nanocrystals with definite morphologies. Finally, to explore the potential applications of CsPbBr3 in white light-emitting diodes (WLEDs), cyan emission of CsPbBr3 NCs (480 nm) is combined with blue, green, and red emissions from commercial powders to achieve white light with excellent vision performance. The device displays a super high color rendering index of 96.5.